The space of justice in Antioch on the Orontes: the dicasterion and the bouleuterion - Silva, Érica Cristhyane Morais da (Romanitas - Revista de Estudos Grecolatinos, 2015)
AntiochontheOrontes is an important city in Late Antiquity and its urban space was the target of several symbolic and materials disputes, reinterpretation and reuse. The representation of urban space in the works of Libânio has been something that recently has fostered enough contributions to our knowledge of the city of Antioch. Nevertheless, it still seems incomplete an understanding about some elements of the Antiochian urban space that relates to legal practices, spaces related to the field of justice. In this paper, we propose to reflect on some elements on the premises of the exercise of Roman legal practices according to Libanius of Antioch given the importance in particular of a mass imprisonment as can be seen in the specific case of the Riot of Statues occurred in 387 AD. Therefore, we aim at reaveling the spaces where legal administrative activities take place in the city of Antioch of Orontes.